2020
DOI: 10.1161/circulationaha.119.039761
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Cardiac Natriuretic Peptide Signaling Promotes Peripartum Cardiomyopathy-Like Remodeling in the Mouse Heart

Abstract: Background: The maternal circulatory system and hormone balance both change dynamically during pregnancy, delivery, and the postpartum period. Although atrial natriuretic peptides and brain natriuretic peptides produced in the heart control circulatory homeostasis through their common receptor, NPR1, the physiologic and pathophysiologic roles of endogenous atrial natriuretic peptide/brain natriuretic peptide in the perinatal period are not fully understood. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…EC- Npr1 -KO and endothelial cell–specific Npr1 –overexpressing mice (EC- Npr1 -Tg) were developed. 13,14…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EC- Npr1 -KO and endothelial cell–specific Npr1 –overexpressing mice (EC- Npr1 -Tg) were developed. 13,14…”
Section: Methodsmentioning
confidence: 99%
“…EC-Npr1-KO and endothelial cell-specific Npr1-overexpressing mice (EC-Npr1-Tg) were developed. 13,14 Preparation of ANP-Conjugated Quantum Dots…”
Section: Animalsmentioning
confidence: 99%
“…Moreover, physiologic cardiac hypertrophy associated with lactation was exaggerated in GC-A −/− mice and correlated with increased cardiac ERK1/2 phosphorylation and activity. 69 Conversely, in GC-A −/− mice, exaggeration of pathologic hypertrophy post-TAC was not dependent on ERK1/2 activity. 9,11 Finally, the ability of ANP to block phenylephrine-dependent increases in neonatal rat CM CSA was shown to require increased, not decreased, ERK1/2 activity, which differs from our model.…”
Section: Discussionmentioning
confidence: 95%
“…Why aldosterone was unchanged in the original GC-A −/− mice 5 and increased in the same mice many years later is not known. 69 A previous study reported that mice with increasing numbers of GC-A alleles have proportionally increased GC-A activity, proportionally increased blood testosterone levels, and proportionally decreased blood pressure. 56 Hence, it was suggested that the GC-A dependent increases in testosterone levels contribute to the hypotension observed in mice with increased GC-A activity.…”
Section: Discussionmentioning
confidence: 98%
“…Bromocriptine (BCR) does not ameliorate cardiac function during l the postpartum term in CM-KO mice. Previous studies have shown that anti-PRL agents, such as BCR, a dopamine D2 receptor agonist, not only improved cardiac function by reducing the plasma 16 K PRL levels 2 but also suppressed cardiac hypertrophy by suppressing the plasma aldosterone and 23 K PRL levels during the lactation term 16 . We examined the effect of BCR in two consecutive deliveries in CTRL or CM-KO mice.…”
Section: Perk Deletion Strongly Modulates Gene Expression In Pp Micementioning
confidence: 99%